1999
DOI: 10.1034/j.1399-3054.1999.105105.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a neutral peroxidase induced by rubbing tomato internodes

Abstract: Rubbing applied to a young tomato internode inhibited the elongation of this internode and increased soluble peroxidase activity. These morphological and biochemical changes were observed both at the site of rubbing (local response) and in the neighbouring internode (systemic response). The cellular, biochemical, and molecular mechanisms leading to inhibition of internode elongation are not fully understood. It was proposed that mechanical stimuli increased the oxidation of IAA, via the induction of specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Calcium probably maintains the conformation of the proteins, whereas Mn 2ϩ could be involved in regulatory processes (Van Huystee et al, 1996). However, Loukili et al (1999) characterized plant peroxidases that were not influenced by these ions. Furthermore, Mn 2ϩ was not detectable in PM from corn roots (Lü thje et al, 1995).…”
Section: Effector Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium probably maintains the conformation of the proteins, whereas Mn 2ϩ could be involved in regulatory processes (Van Huystee et al, 1996). However, Loukili et al (1999) characterized plant peroxidases that were not influenced by these ions. Furthermore, Mn 2ϩ was not detectable in PM from corn roots (Lü thje et al, 1995).…”
Section: Effector Studiesmentioning
confidence: 99%
“…Most peroxidases from plants and animals seemed to have high temperature optima and show high thermal stabilities (Bakardjieva et al, 1996;Madhavan and Naidu, 2000). Apoplastic, cytosolic, and soluble peroxidases of several plant tissues showed temperature optima between 30°C and 60°C, the most between 50°C and 60°C (Soda et al, 1991;Bakardjieva et al, 1996;Nair and Showalter, 1996;Bernards et al, 1999;Loukili et al, 1999). Due to the fact that pmPOX1 had a lower temperature optimum than pmPOX2, the latter enzyme seemed to be more stable (Fig.…”
Section: Temperature Optima and Thermal Stabilitymentioning
confidence: 99%
“…Many authors have reported the appearance or disappearance of specific peroxidase isoforms during a particular process or in a particular localization (e.g. Loukili et al, 1999;Allison and Schultz, 2004). Nevertheless it is generally difficult to associate the band observed on an isoelectric focusing (IEF) gel with a particular protein mainly because protein purification is not straightforward.…”
Section: The Diverse Functions Of Class III Peroxidasesmentioning
confidence: 99%
“…Peroxidase activity in the extracts was measured as described by Loukili et al (1999) using 24 mM guaiacol and 60 mM hydrogen peroxide in a spectrophotometer, recording changes in absorbance (470 nm). Polyphenoloxidase activity in the extracts was measured as proposed by Shin et al (1997) in a spectrophotometer as well, recording the changes in absorbance (410 nm), using 100 mM 4-methylcatechol as substrate and 0.2 M phosphate buffer pH 6.5.…”
Section: Enzyme Assay For Ppo and Pomentioning
confidence: 99%